Long term compositional profiling of historical tokaji aszú wines - Ágota Ragyák; Zsófi Sajtos; Edina Baranyai; Elemér László (npj Science of Food)
Abstract This study examines the elemental composition of unique Tokaji aszú wines produced between 1999 and 2019, representing the longest period for this wine type to date. Twenty-one samples were analyzed using ICP-OES and FTIR techniques. Multivariate statistical analysis revealed significant variations linked to vintage, annual precipitation, sunshine hours, and temperature. Potassium and chromium levels showed strong negative correlations with age, while calcium exhibited a slight increasing trend. FTIR analysis highlighted compositional differences driven by environmental factors, with PCA clustering vintages based on similar weather patterns. These findings emphasize the influence of environmental conditions on the elemental profile of aged aszú wines, offering insights into historical agricultural practices and environmental shifts. The study underscores the value of long-term wine analysis for understanding climate impacts, optimizing future wine production, and preserving the heritage of traditional viticulture. It highlights elemental profiling as a promising tool for historical analysis, environmental assessment, and sustainable viticultural planning.